Generational Differences in Subjective Well-Being in Australia - Botha, Ferdi; Vera-Toscano, Esperanza (My University, 2022)
We test for differences in subjective well-being across four pre-defined generations in Australia born between 1928 and 1994: The Lucky Generation, Baby Boomers, Generation X, and Generation Y. We focus on overall life satisfaction and range of domain satisfactions. We find that Baby Boomers are less satisfied with life than thosce born before and after them. We observe similar patterns when considering domains such as finances and housing. However, differences in satisfaction with employment opportunities show the opposite pattern, with Baby Boomers and Generation X’s reporting higher satisfaction as compared to the Lucky Generation and especially those from Generation Y. Family and labour marketcv status have greater effects than cohort of birth on many of the domains studied; however, the cohort effects are significant and non-negligible, particularly concerning satisfaction with life, employment opportunities, and housing.
Applied Research in Quality of Life
Keywords: Health and wellbeing